2004
DOI: 10.1021/es0497678
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of a Mixture of Dissimilarly Acting Substances to Natural Algal Communities:  Predictive Power and Limitations of Independent Action and Concentration Addition

Abstract: Predictive studies of chemical mixtures are typically based on experiments with single species. To study the applicability of the concepts of independent action (IA) and concentration addition (CA) on a multispecies level, the carbon fixation of natural algal communities under toxicant exposure was studied. The presented study focused on a mixture of six dissimilarly acting substances. Conceptual reasoning as well as empirical evidence from single-species tests suggest that IA is more appropriate for this type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(123 citation statements)
references
References 18 publications
4
111
2
3
Order By: Relevance
“…As a consequence, the models are not suitable for describing phenomena such as stimulating effects at low concentrations (i.e. hormesis) or the occurrence of thresholds (Backhaus et al, 2004). Moreover, as shown in the present work, when the maximal plateau of VTG induction cannot be obtained and no appropriate regression analysis can therefore be fitted to the data, the application of the CA model is limited.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As a consequence, the models are not suitable for describing phenomena such as stimulating effects at low concentrations (i.e. hormesis) or the occurrence of thresholds (Backhaus et al, 2004). Moreover, as shown in the present work, when the maximal plateau of VTG induction cannot be obtained and no appropriate regression analysis can therefore be fitted to the data, the application of the CA model is limited.…”
Section: Discussionmentioning
confidence: 79%
“…In fact, the CA model has been suggested as the pragmatic default approach when calculating the quantitative effects of any combination of agents, irrespective of the (dis)similarity of its components (de Zwart and Posthuma, 2005). However, due to the weakness of the mathematical formula and the varying natures of the chemicals tested, no concept currently provides a ''general solution" for assessing the interactions between estrogenic chemicals (Thorpe et al, 2001;Altenburger et al, 2004;Backhaus et al, 2004 Vitellogenin (VTG) is normally synthesized in mature female fish under the control of estrogen, mediated by estrogen receptors (ERs), and is then incorporated into growing oocytes. However, since both sexes carry ERs and the VTG gene, males or juveniles can be induced to synthesize VTG after exposure to estrogen or estrogen-mimics (Denslow et al, 1999;Brion et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…RA underestimated the effect of all 16 mixtures, demonstrating that it was unsuitable for assessing the effects of estrogenic chemicals in this assay. This may be because of the fundamentals of the yeast assay: RA model is not the optimal choice when only similarly acting chemicals can activate the yeast system (Backhaus et al, 2004;Drescher and Boedeker, 1995;Faust et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These facts make them ideal candidates for testing mixture models based on the chemical mode of action and understanding the physiological mechanisms behind possible interactions [85,90]. Mixture toxicity studies focused on single species [85,86], natural communities in laboratory experiments [3,82,91], or outdoor microcosms and mesocosms [83,[92][93][94] data. Many reviews and critical analysis have shown that synergistic interactions within pesticide mixtures and realistic low-dose chemical mixtures in species are a rather rare phenomenon, constituting very low percentages of the tested mixture combinations and often occurs at high concentrations [87,[95][96][97][98][99][100][101].…”
Section: Tlili Et Al (2011) [89]mentioning
confidence: 99%